Russian Aviation and Air Power in the Twentieth Century. - Higham, Robin, 1925-2015.; Greenwood, John T.; Hardesty, Von, 1939- (London ; New York : Routledge, Taylor & Francis Group, 2014)
In the light of new archival material the editors take a fresh look at Russian aviation in the twentieth century. Presenting a comprehensive view of Russian aviation, from its genesis in the late czarist period to the present era, the approach is essentially chronological with a major emphasis on the evolution of military aviation. The contributions are diverse, with appropriate attention to civilian and institutional themes.
9 Air Combat on the Periphery: The Soviet Air Force in Action during the Cold War, 1945-8910 The Rise and Fall of Aeroflot: Civil Aviation in the Soviet Union, 1920-91; Epilogue; Acknowledgements and Further Reading; Index.
Includes bibliographical references and index.
Print version record.
Keywords: Aeronautics -- Soviet Union -- History; Aeronautics, Military -- Soviet Union -- History; TECHNOLOGY & ENGINEERING -- Engineering (General); Aeronautics; Aeronautics, Military; Soviet Union; History